Gender Diversity dan Kinerja Keuangan - Novian Apriansyah; Sherla Aprilia Kusumajaya; Ahmad Dhani; shintia Permata sari (Journal of Student Research, 2025)
This study aims to synthesize the results of previous research on gender diversity and financial performance through Systematic Literature Review (SLR). This research using SLR presents quantitative data to determine the development of gender diversity issues. There are several parameters used, namely journal sources, variable mapping and theory as well as fields of science, research approaches and companies. The results of this study show that there are 30 articles originating from accredited national and national journals during the period 2020-2024. The topic of financial performance associated with environmental performance, firm value, Environmental Social Governance (ESG), capital structure, Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), fair value, accounting conservatism. which continues to grow. Upperchelon theory is the most widely used theory as well as the dominant use of quantitative methods in financial performance research. Manufacturing companies are companies that research financial performance issues